The current status of contribution activities in Japan for LISA. (14th August 2020) - Izumi, Kiwamu; Sago, Norichika; Akutsu, Tomotada; Ando, Masaki; Fujita, Ryuichi; Fukunabe, Kenji; Kita, Naoki; Kobayashi, Masato; Komori, Kentaro; Michimura, Yuta; Musha, Mitsuru; Nagano, Koji; et al.
Abstract: LISA is a space gravitational-wave mission that will open the unexplored gravitational-wave frequency window at around millihertz, shedding light on the study of supermassive black holes and the nature of gravity. The LISA project has been propelled by international collaboration in order to maximize the scientific outcome. With the aim of making scientifically important contributions to LISA, instrument and science groups were newly formed in Japan. This article summarizes the current status of the contribution activities conducted by each group to date, highlighting a few selected topics including the development of photoreceivers and theoretical studies on compact binaries and extreme mass ratio inspirals.